Strategi Manajemen Media Penyiaran Music Television (MTV) Networks United Kingdom & Ireland - Murfianti, Fitri; Sulistya, Ari Puguh (Capture : Jurnal Seni Media Rekam, 2014)
Music Television (MTV) Networks UK & Ireland is one of the television stations that have credibility and existence in the history of international broadcast world. Its existence and credibility that exists since 1997 until today is one of the evidence of its good works and management system. Formulation on this research focuses on how the broadcasting management strategies of MTV Networks UK & Ireland is explored by 3 aspects: marketing, program, and technic. The purpose of this research is to describe the broadcasting management systems and strategies based on those three aspects. This research uses qualitative methods and theoretical basis that appropriate for the purpose of the research. The data written on this research are based on interviews, observation, and documents review. The result of this research proved that MTV Networks UK & Ireland has a great discipline management strategy seen from the aspects: program, marketing and technique. Each aspect is bound to each other, without one of them the success of broadcast management strategy on MTV Networks UK & Ireland is hard to reach . Keywords: strategy, broadcast, MTV Networks UK & Ireland, Music Television